Characterization of mutations in the reverse transcriptase region of hepatitis B virus in treated and untreated chronic hepatitis B patients. (24th November 2020) - Zou, Weihua; Qian, Fuchu; Jin, Fang; Li, Dongli; Chen, Jing
Abstract: Background: The reverse transcriptase (RT) region of the hepatitis B virus (HBV) is the target of antiviral treatment. However, the discrepancy in RT mutations between nucleos(t)ide analogue (NA)-treated and -untreated chronic hepatitis B (CHB) patients is un clear. Methods: Serum samples were collected from 119 NA-treated and 135 NA-untreated patients. The sampling time was decided by the clinician. Full-length HBV RT regions were amplified using nest polymerase chain reaction. The mutations within the RT region were analysed by direct sequencing. Results: The incidence of RT mutations in treated patients was higher than that in untreated patients (p<0.05). The classic drug-resistant mutations were detected in 44.5% (53/119) of treated patients, which was significantly higher than in untreated patients (6.7% [9/135]) (p<0.05). The non-classical mutations showed their complexity and diversity in both patient groups. Multiple mutations (three or more) were more frequent in treated patients than in untreated patients (p<0.05). Several novel mutations might be related to NA resistance. Conclusions: The selection pressures of NAs accelerated the development of RT mutations, especially within the functional domain. Mutations in the RT region occurred not only at classical sites, but also at other non-classical sites, which might be related to drug resistance and/or viral replication. The biological function and fitness of HBV isolates harbouring these novel mutations need further in vitro and in vivo verification experiments.